The Relationship between the Role of Health Workers in Exclusive Breastfeeding in the Working Area of PUSKESMAS Pampang Makassar - Hamang, Sitti Hadriyanti; Nurana, Sitti; Nurhayati, Nurhayati (JURNAL ILMIAH OBSGIN : Jurnal Ilmiah Ilmu Kebidanan & Kandungan P-ISSN : 1979-3340 e-ISSN : 2685-7987, 2023)
Mother's milk is a baby who has only been given breast milk for 6 months without additional fluids and additional solid food, for example formula milk, oranges, honey, tea and water, such as bananas, milk porridge, biscuits, rice porridge and team rice except vitamins. and medicine. Exclusive breastfeeding for 6 months and continuing to provide breast milk until 11 months and complementary foods at 6 months can reduce under-five mortality by around 13%. Around 16% of neonatal deaths can be prevented if babies are breastfed from the first day of birth and babies who are breastfed within the first hour can reduce the risk of death by around 22%. In the working area of ​​the Pampang Health Center, Makassar City, it is one of the areas that is still considered low in achieving exclusive breastfeeding, namely less than 60%. This data was obtained from the results of maternal and child health reports in 2014. The type of research used is a quantitative analytical survey with a cross sectional study approach.The population in this study was all mothers who had babies aged 6-11 months in the Pampang Makassar Health Center working area, totaling 106 mothers. The sample in this study were mothers who had babies aged 6-12 months who were willing to take part in this research. The sample size in this study was calculated using the Lemeshow formula so that there were 50 respondents. The conclusion of this research is that exclusive breastfeeding in the working area of ​​the Pampang Health Center, Makassar City is still relatively low (58%) and there is no relationship between the role of health workers and exclusive breastfeeding for babies 0-6 months in Pampang sub-district, the Pampang Makassar Health Center working area and the value The significance obtained was 0.684. It is hoped that the public, especially pregnant women, will carry out pregnancy and childbirth examinations at the health services that have been provided so that important information about maternal and child health is easily obtained, so that it is hoped that it can increase the coverage of exclusive breastfeeding. A part from that, it is hoped that health workers will further increase their role in providing information or education regarding exclusive breastfeeding so that the success of exclusive breastfeeding can run optimally and successfully.